Unveiling the Distinctive Traits of Aedes aegypti and Aedes albopictus Mosquito Larvae: A Remarkable Entomological Exploration for dengue fever - Astuti, Aldiana; Rolanda, Rolanda (ANJANI Journal (Medical Science & Healthcare Studies), 2023)
ABSTRAKPendahuluan: Penyakit Demam Berdarah Dengue (DBD) merupakan ancaman global yang disebabkan oleh virus yang ditularkan melalui gigitan nyamuk Aedes aegypti dan Aedes albopictus. Penelitian ini bertujuan untuk mendalami karakteristik larva kedua jenis nyamuk tersebut melalui pendekatan entomologi, dengan tujuan memahami pola perindukan dan perilaku habitatnya. Metode: Penelitian ini mengadopsi pendekatan eksploratif entomologi dengan teknik pengambilan sampel larva menggunakan metode simple random sampling. Fokus utama penelitian adalah pada identifikasi ciri khas larva Aedes aegypti dan Aedes albopictus serta distribusi perindukannya di area penelitian. Hasil: Hasil penelitian mengungkapkan ciri khas larva Aedes aegypti dan Aedes albopictus yang mencolok, dengan perbedaan dalam pola perindukan dan prevalensi di berbagai lingkungan. Larva Aedes aegypti cenderung mendominasi di ruangan, sementara larva Aedes albopictus lebih sering ditemukan di luar ruangan. Temuan ini memberikan wawasan mendalam mengenai adaptasi kedua jenis nyamuk terhadap lingkungan sekitarnya. Kesimpulan: Eksplorasi entomologi ini memberikan pemahaman yang lebih mendalam mengenai ciri khas larva Aedes aegypti dan Aedes albopictus, serta distribusi perindukannya di lingkungan sekitar. Penelitian ini memberikan dasar untuk pengembangan strategi pengendalian vektor yang lebih efektif dalam upaya pencegahan Demam Berdarah Dengue. Hasil ini diharapkan dapat menjadi landasan bagi intervensi yang tepat dan berkelanjutan untuk mengurangi risiko penularan DBD. ABSTRACTIntroduction: Dengue Hemorrhagic Fever (DHF) is a global threat caused by viruses transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. This research aims to delve into the characteristics of larvae of both mosquito species through an entomological approach, with the goal of understanding their breeding patterns and habitat behavior. Methodology: The study adopts an exploratory entomological approach with larval sampling using the simple random sampling method. The primary focus of the research is on identifying the distinctive features of Aedes aegypti and Aedes albopictus larvae, as well as their distribution of breeding sites within the study area. Results: The research reveals striking characteristics of Aedes aegypti and Aedes albopictus larvae, showing differences in breeding patterns and prevalence across various environments. Aedes aegypti larvae tend to dominate indoor locations, while Aedes albopictus larvae are more commonly found in outdoor settings. These findings provide profound insights into the adaptation of both mosquito species to their surrounding environments. Conclusion: This entomological exploration offers a deeper understanding of the distinctive characteristics of Aedes aegypti and Aedes albopictus larvae, along with the distribution of their breeding sites in the surrounding environment. The research provides a foundation for the development of more effective vector control strategies in the effort to prevent Dengue Hemorrhagic Fever. These results are expected to serve as a basis for appropriate and sustainable interventions to reduce the risk of Dengue transmission.